Diurnal Changes in Hypoxia Shape Predator-Prey Interaction in a Bird-Fish System - Lukas, Juliane; Auer, Felix; Goldhammer, Tobias; Krause, Jens; Romanczuk, Pawel; Klamser, Pascal; Arias-Rodriguez, Lenin; Bierbach, David (Frontiers in Ecology and Evolution, 2021)
Animals often face changing environments, and behavioral flexibility allows them to rapidly and adaptively respond to abiotic factors that vary more or less regularly. However, abiotic factors that affect prey species do not necessarily affect their predators. Still, the prey’s response might affect the predator indirectly, yet evidence from the wild for such a classical bottom-up effect of abiotic factors shaping several trophic levels remains sparse. In many aquatic environments, daily changes in oxygen concentrations occur frequently. When oxygen levels drop to hypoxic levels, many fishes respond with aquatic surface respiration (ASR), during which they obtain oxygen by skimming the upper, oxygenated surface layer. By increasing time at the surface, fish become more vulnerable to fish-eating birds. We explored these cascading effects in a sulfidic spring system that harbors the endemic sulphur molly (Poecilia sulphuraria) as prey species and several fish-eating bird species. Sulfide-rich springs pose harsh conditions as hydrogen sulfide (H2S) is lethal to most metazoans and reduces dissolved oxygen (DO). Field sampling during three daytimes indicated that water temperatures rose from morning to (after)noon, resulting in the already low DO levels to decrease further, while H2S levels showed no diurnal changes. The drop in DO levels was associated with a decrease in time spent diving in sulphur mollies, which corresponded with an increase in ASR. Interestingly, the laboratory-estimated threshold at which the majority of sulphur mollies initiate ASR (ASR50: <1.7 mg/L DO) was independent of temperature and this value was exceeded daily when hypoxic stress became more severe towards noon. As fish performed ASR, large aggregations built up at the water surface over the course of the day. As a possible consequence of fish spending more time at the surface, we found high activity levels of fish-eating birds at noon and in the afternoon. Our study reveals that daily fluctuations in water’s oxygen levels have the potential to alter predator-prey interactions profoundly and thus highlights the joined actions of abiotic and biotic factors shaping the evolution of a prey species.